The importance of comparative fiqh in contemporary issues / Wan Nurul Balqis Zaihan Marican … [et al.] - Zaihan Marican, Wan Nurul Balqis; Md Rahim, Nur Auni Huda; Zahari, Nurul Ashikin; Mahassan, Muthmainnah (2023)
Islam is a religion and a way of life that is syumul or comprehensive, where all its rules have been determined in all aspects of human life ranging from the question of faith, worship, and morality, to the affairs of society and statehood which range from economic, educational, political and social domains. The source of the ruling from al-Quran and al-Sunnah is the best guide to mankind where it is the revelation of Allah SWT which contains the legal explanation for every question in everyday life. The sanctioning of the ruling found in the Quran and alSunnah is included in two components which are Al-Thawabit (permanent and eternal) and almutaghayyirat (which can change). Al-Thawabit is the fundamental Islam which is the pillar, foundation, and principle of religion which does not change until the day of Resurrection, while al-mutaghayyirat is the branches or furu' ruling that can change according to the circumstances of the atmosphere and times.